Multidisciplinary aerodigestive program at a children’s hospital: A protocol for a prospective observational study - Mireu Park; Seung Kim; Eunyoung Kim; Ga Eun Kim; Jae Hwa Jung; Soo Yeon Kim; Min Jung Kim; Da Hee Kim; Sowon Park; In Geol Ho; Seung Ki Kim; Sangwon Hwang; et al. (PLoS ONE, 2021)
Background Children with complex chronic multisystemic diseases frequently require care from multiple pediatric subspecialists. The aerodigestive program is a multidisciplinary program that diagnoses and treats pediatric patients with complex multi-systematic problems affecting airway, breathing, feeding, swallowing, or growth. The aim of this study is to present the protocol of the aerodigestive program of a children’s hospital. Methods and design This study is a prospective study to evaluate and compare the overall improvement of patients’ objective and subjective conditions before and after the AeroDigestive Team (ADT) program. Among children from 1 month to 18 years of age, patients with complex problems of the airway, breathing, feeding, swallowing, or growth meeting at least two parameters of the inclusion criteria were enrolled. The overall process included referral based on the inclusion criteria, enrollment of ADT program with informed consents, interview and questionnaire for assessing patients’ medical condition, prescheduling appointment, multi-specialists’ evaluation, monthly team meetings, wrap-up discussion with the patients and family, therapeutic intervention, and follow-up at 6 months with the assessment of outcome measures. The outcome was evaluated objectively and subjectively. The objective outcome measure was divided into surgical or medical intervention, assessment of changes in medical condition, and follow-up study. Both caregiver interviews and questionnaires using a scoring system were used as subjective outcome measures before and after the ADT program. Children were scheduled to be followed-up at 6 months after the interventions or ADT meeting. Discussion The aerodigestive program is expected to provide comprehensive and multidisciplinary management of children with complex airway and digestive tract disorders.